2011
DOI: 10.1111/j.1467-9604.2011.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of education in the treatment of offenders

Abstract: This article considers an aspect of inclusive education that has received relatively limited exposure: the challenges involved in meeting the educational needs of offenders in prisons. It does this by taking the example of Serbia, where recent changes in legislation have ensured the educational rights of inmates. It then looks at possible ways in which more inclusive approaches to the education of inmates in prison might be developed in Serbia by illustrating some successful initiatives from the United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Each unit housed approximately 20 inmates. Because research has shown that literacy levels of inmates tend to be deficient (Caddick & Webster, 1998; Davies, Lewis, Byatt, Purvis, & Cole, 2004; Jovanić, 2011), the staff member also read the recruitment form aloud to the groups of inmates housed in the various units and provided an opportunity for them to ask questions. Inmates were informed that the provision of a signature on the recruitment form indicated that they were interested in participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…Each unit housed approximately 20 inmates. Because research has shown that literacy levels of inmates tend to be deficient (Caddick & Webster, 1998; Davies, Lewis, Byatt, Purvis, & Cole, 2004; Jovanić, 2011), the staff member also read the recruitment form aloud to the groups of inmates housed in the various units and provided an opportunity for them to ask questions. Inmates were informed that the provision of a signature on the recruitment form indicated that they were interested in participating in the study.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Aliyu et al, (2016) opined that since the inception of prison service in Nigeria, there have been little or no systematic educational provisions for inmates due to limited resource allocation. Jovanić andassociates (2011, 2019) stated that reformative education in prison should be diversified, and should focus on training convicted prisoners. It will, in the end, enable them to earn an honest living in the community.…”
Section: Department Of Educationmentioning
confidence: 99%
“…At the same time, it also reduces the feeling of alienation that inmates tend to experience while in prison. The resulting improvement in social skills can make it easier for inmates to find and hold a job upon release, which in turn reduces their likelihood of re-offending or returning to crime (Taib, 2012;Jovanić, 2011;Jovanić et al, 2019). Volume 3 Issue 1, 2020 International Crisis Group (2011) opined that reformative education is central to curbing rising crime and militancy, fixing a deteriorating criminal justice system, and enforcing the rule of law.…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes this takes the form of thematic country‐focused issues (as in the case of Northern Ireland in 2006 or New Zealand in 2011). More regularly, Support for Learning carries individual articles from authors from across the globe – examples of this in recent years have been Greece (Giannouli and Pavlidis, ), Serbia (Jovanovic, ) and Hong Kong (Chen Zhang and I‐Hwey Wu, ).…”
mentioning
confidence: 99%